Fractional esterification rate of cholesterol and ratio of triglycerides to HDL-cholesterol are powerful predictors of positive findings on coronary angiography - Frohlich, Jiří; Dobiášová, Milada (Clinical chemistry, 2003)
BACKGROUND: We examined the predictive value of various clinical and biochemical markers for angiographically defined coronary artery disease (aCAD). Specifically, we assessed the value of the ratio of plasma triglyceride (TGs) to HDL-cholesterol (HDL-C) and the fractional esterification rate of cholesterol in plasma depleted of apolipoprotein B (apoB)-containing lipoproteins (FER(HDL)), a functional marker of HDL and LDL particle size. METHODS: Patients (788 men and 320 women) undergoing coronary angiography were classified into groups with positive [aCAD(+)] and negative [aCAD(-)] findings. Patient age, body mass index, waist circumference, blood pressure (BP), medications, drinking, smoking, exercise habits, and plasma total cholesterol (TC), LDL-cholesterol (LDL-C), HDL-unesterified cholesterol, HDL-C, TGs, FER(HDL), apoB, log(TG/HDL-C), and TC/HDL-C were assessed. Lipids and apoproteins were measured by standard laboratory procedures; FER(HDL) was determined by a radioassay. RESULTS: Members of the aCAD(+) group were older and had a higher incidence of smoking and diabetes than those in the aCAD(-) group. The aCAD(+) group also had higher TG, apoB, FER(HDL), and log(TG/HDL-C) and lower HDL-C values. aCAD(+) women had greater waist circumference and higher plasma TC and TC/HDL-C. aCAD(+) men, but not women, had higher plasma LDL-C. In the multivariate logistic model, the significant predictors of the presence of aCAD(+) were FER(HDL), age, smoking, and diabetes. If only laboratory tests were included in the multivariate logistic model, FER(HDL) appeared as the sole predictor of aCAD(+). Log(TG/HDL-C) was an independent predictor when FER(HDL) was omitted from multivariate analysis. CONCLUSIONS: FER(HDL) was the best laboratory predictor of the presence of coronary atherosclerotic lesions.
Keywords: esterifikace; Male; Cholesterol, LDL; biologické markery; HDL-cholesterol; Coronary Artery Disease; Biomarkers; regresní analýza; LDL-cholesterol; Cholesterol, HDL; Adolescent; Cholesterol; Adult; Aged; dospělí; mužské pohlaví; senioři; Coronary Angiography; triglyceridy; nemoci koronárních tepen; mladiství; Multivariate Analysis; cholesterol; senioři nad 80 let; lidé; ženské pohlaví; Esterification; Humans; Aged, 80 and over; prediktivní hodnota testů; koronární angiografie; Triglycerides; Regression Analysis; multivariační analýza; Female; lidé středního věku; Predictive Value of Tests; Middle Aged